Closing the Gap: Increasing Vocational Awareness in the Science Classroom - Uhlemann, Max R.; France, M. Honoré; Stronck, David R. (Canadian Journal of Counselling and Psychotherapy, 2012)
In this article the authors, two counsellors and a teacher, collaborate to propose a role for the counsellor in implementing career education in the academic classroom. Specific attention is directed to the science classroom. A brief view of the career education concept is presented. This is followed by an examination of the science teacher's responsibility in assisting students to understand science and technology and its career implications. It is proposed that the counsellor is in a unique position to provide career education consultation to the science teacher. The argument infavor of a cooperative approach to facilitating vocational awareness is made, andpractical ideas for integrating career education into the science classroom are presented.